Navigating the path to sustainable supply chains: A quantitative study of barriers and enablers in South African listed companies - Kato, Ahmed I; Manchidi, Ntise H (International Journal of Management and Sustainability, 2025)
Recently, large corporations have faced mounting pressure to adopt manufacturing and operational practices that prioritize environmental responsibility and societal needs, paving the way for a sustainable future. Implementing sustainable supply chain management (SSCM) practices can enhance business sustainability and provide a competitive edge as companies are increasingly accountable for the environmental and social impacts. This study aims to evaluate the enablers and barriers of SSCM implementation in South Africa's listed companies. We analyzed panel data obtained from 46 premier listed firms on the Johannesburg Stock Exchange (JSE) employing a quantitative methodology alongside structural equation modelling. This research analyzes various factors influencing supply chains including government policy, stakeholder engagement, ethical sourcing, collaborative partnerships and the role of digitalization. The research findings underscore specific barriers, including market volatility, fluctuations in energy prices and escalating labour costs. In addition, the study identifies facilitators, particularly the growing demand for enhanced digitalization within procurement practices in public sector supply chain management. The findings suggest a growing imperative for private enterprises and governmental bodies to advocate for sustainable practices within the sector. Additionally, they underscore the distinct challenges faced by JSE-listed companies in the implementation of SSCM.